Carbon Nanotube Networks as Thermally Conducting Layers - Juteräng, David (My University, 2022)
Flexible and thermally conductive materials with microfabricated structures are important in a number of different research fields. Different approaches for integration of such materials into functioning devices have been implemented in a plethora of ways. Carbon nanotube networks have been the subject of many studies due to their remarkable physical properties, including high thermal conductivity, high electron mobility, high Young’s modulus and their flexibility, but challenges still remain. One hurdle to overcome is the lack of efficient bonds between nanotubes in meshes. In this project, the viability of a nickel/carbon nanotube network have been investigated in the context of a potential thermal spreading hybrid material. Carbon nanotubes of with different lengths were grown on silicon substrates, dispersed in acetone and mixed into solutions containing Nickel-oxide particles. The blends were deposited onto new Silicon substrates where they formed networks. The Nickel particles stuck to strands and bundles of nanotubes, forming bridges between them. Thermal treatment of the networks were performed at different time scales in order to study the effects of annealing on the networks. The characteristics of the Ni/CNT networks were finally investigated using scanning electron microscopy and Raman spectroscopy in order to study potential changes within them. An increase of the D-peak/G-peak intensity ratio corresponding to longer thermal treatment of the substrates were concluded to be a plausible indicator of increased bonding between the Ni-particles and CNTs. In addition, a simulation was made of a CNT-CNT electron tunneling junction. This was done in order to provide the theoretical backround for the challenges regarding CNT meshes. The lack of chemical bonds between tubes were calculated to increase the resistance of a square CNT thin film by approximately 150%.
Keywords: CNT, Ni, Thin film, Network, Mesh, Hybrid material, Thermal Conductance, Tunneling, Junction, Raman spectroscopy